Ocenka nekotorych biochimiceskich pokazatelej krovi futbolistov v sorevnovatel'nom periode sportivnoj podgotovk - Nikityuk, D. B.; Radzhabkadiev, R. M.; Soto, S. H.; Lavrinenko, S. V.; Sokolov, A. I.; Kobelkova, I. V.; Vybornaya, K. V.; Semenov, M. M.; Klochkova, S. V.; Tutov, A. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
We examined 22 professional football players in the competitive period. The average age of the subjects was 24 ± 5.3 years (18-29 years). The survey was conducted the day after the match in the regular season of the professional football league. We studied some biochemical parameters in the blood serum of athletes (activity of alaninamino- and aspartate-aminotransferase (ALT, AST), the concentration of glucose, total protein, albumin, globulins, creatinine, uric acid, total cholesterol, high-density lipoproteins and low-density lipoproteins). The De Ritis coefficient was calculated by the ratio of AST / ALT activity. We found 12 athletes (n = 54.5%) excess of AST activity by 30% relative to physiological norms. The de Ritis coefficients in 4 athletes (n = 18%) were slightly higher than the physiological norm, and in 1 athlete - at a critical level. Only 5 athletes (23%) creatinine level exceeded the reference intervals. Uric acid in 8 examined athletes (36%) exceeded the physiological norm by an average of 11%. Analysis of the lipid profile showed a slight excess of total cholesterol and high-density lipoproteins in 5 and 7 athletes, respectively. An individual analysis of the studied parameters did not reveal significant differences between the athletes. This is also confirmed by low values of the coefficient of variation of biochemical parameters (< 30%). The results obtained testify to the high degree of fitness of athletes and the high level of their adaptive potential.